Evaluation of 15 primitive races of cotton for antibiosis effect on cotton leafworm - Penna, Julio C. V.; Fallieri, Joel; Ferreira, Levi (Pesquisa Agropecuaria Brasileira, 2014)
Fifteen primitive races of cotton (‘T’ race stocks) were evaluated under controlled conditions, for antibiosis effect on larvae and pupae of cotton leafworms, in 1983, in Centro Regional de Pesquisa do Triângulo e Alto Paranaíba (CRTF-EPAMIG), MG, Brazil. Larvae received a leaf diet of the germplasms studied, during twelve days, and then were weighed. Races T-295, T-284 and T-254 were responsible for the attainment of the lightest larvae, respectively 0.066, 0.078 and 0.100 g. Races T-169, T-133, T-25 and T-119 produced the lightest pupae, respectively 0.184, 0.188, 0.196 and 0.198 g. Correlation between larva and pupa weight was not significant.